Morphological and performance characteristics of elite Colombian speed skaters - Boryi A Becerra-Patiño; Armando Monterrosa-Quintero; Diego Armando González Valenzuela (CV. FOUNDAE, 2026)
Background: Inline speed skating demands explosive strength and specific anthropometric profiles, yet studies on sex-based morphological and functional differences among Latin American skaters are scarce. This exploratory cross-sectional study aimed to characterize physical performance and anthropometric variables by sex in elite Colombian junior inline speed skaters. Aims: The primary objective of this exploratory cross-sectional study was to characterize the anthropometric profiles and physical performance variables by sex in a sample of elite Colombian junior inline speed skaters. Methods: Twenty-three elite skaters (12 females, 11 males; aged 16-21 years) were assessed. Anthropometric profiling followed ISAK guidelines, measuring skinfolds, girths, and breadths. Physical performance and explosive strength were evaluated using various jump tests (SJ, CMJ, SLCMJ, and continuous jumps) via the My Jump Lab application. Results: Marked sexual dimorphism was observed in body composition: females exhibited higher subcutaneous adiposity (fat mass), whereas males demonstrated greater muscle mass and skeletal robustness. However, differences in explosive performance and functional metrics between sexes were unexpectedly modest. Conclusions: Elite female skaters achieve functional outcomes comparable to those of males despite marked morphological differences. These findings indicate that higher body fat limits jumping capacity, highlighting the need for systematic body composition monitoring and the development of sex-specific training strategies.